The Effects Of Audio-Visual Aids On Listening Comprehension - Nabila Arrahma; Siti Rahimah Harahap; Marhamah Salwa; Yani Lubis (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Listening comprehension is the ability to understand spoken information. This ability is very important for various aspects of life, such as education, work and daily life. This study aims to investigate the effect of using audio visual aids (AVA) on listening comprehension. A total of 6 high school students were involved in this research. They were divided into two groups, namely the control group and the experimental group. The control group did not use AVA, while the experimental group used AVA in listening learning. The results showed that the experimental group that used AVA had better listening comprehension than the control group that did not use AVA. The difference in listening comprehension between the two groups was statistically significant. The results of this study indicate that AVA can improve listening comprehension. AVA can help students to better understand the information spoken, because AVA can provide a visualization of that information.